Lutherans in the Poznań province: biological dynamics of the Lutheran population in the 19th and early 20th centuries - Liczbińska, Grażyna (Schriftenreihe Herodot, 2015)
"This book focuses on the biological dynamics of the Lutheran populations in the Poznan province in the second half of the 19th and early 20th centuries, its ecological and socio-cultural factors and changes over time. The analysis is based on data derived from registers of selected Lutheran parishes and Prussian statistics for the region as a whole. This material permitted a detailed study of mortality, including infant deaths, marital fertility and illegitimacy, patterns of marriage, and the state of and changes in the gene pool of the Lutheran communities in the Poznan province. Such components of their biological dynamics as mortality and fertility were strongly influenced by broadly understood cultural and environmental factors. A gradual decline in both mortality and fertility figures over time observed among the Lutherans under study was a phenomenon characteristic of the Polish lands of that time, including those under Prussian rule, strictly associated with improvement in the quality of life, medical care and ecological conditions in the province in the late 19th century. The analysis of the state of and changes in the gene pool of the Lutheran communities in the province leads to the conclusion that migratory movement was the main factor dynamizing their gene pools in the 19th and early 20th centuries."--Publisher's website